2005
DOI: 10.1038/nature03341
|View full text |Cite
|
Sign up to set email alerts
|

Ancient co-speciation of simian foamy viruses and primates

Abstract: Although parasite-host co-speciation is a long-held hypothesis, convincing evidence for long-term co-speciation remains elusive, largely because of small numbers of hosts and parasites studied and uncertainty over rates of evolutionary change. Co-speciation is especially rare in RNA viruses, in which cross-species transfer is the dominant mode of evolution. Simian foamy viruses (SFVs) are ubiquitous, non-pathogenic retroviruses that infect all primates. Here we test the co-speciation hypothesis in SFVs and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
223
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 249 publications
(254 citation statements)
references
References 25 publications
30
223
1
Order By: Relevance
“…Molecular dating showed that the yucca-yucca moth association arose at least 40 million years ago (Pellmyr 2003) and long-term co-divergence was recently reported for Simian foamy RNA viruses and old World primates (Switzer et al 2005). The phylogenetic trees were remarkably congruent in both branching order and divergence times over 30 million years, strongly supporting co-speciation in this host-parasite system.…”
Section: Co-divergence In the Fig-wasp Symbiosis N Rønsted And Othermentioning
confidence: 66%
“…Molecular dating showed that the yucca-yucca moth association arose at least 40 million years ago (Pellmyr 2003) and long-term co-divergence was recently reported for Simian foamy RNA viruses and old World primates (Switzer et al 2005). The phylogenetic trees were remarkably congruent in both branching order and divergence times over 30 million years, strongly supporting co-speciation in this host-parasite system.…”
Section: Co-divergence In the Fig-wasp Symbiosis N Rønsted And Othermentioning
confidence: 66%
“…NA, not applicable. (36); however, this patient sample contrasts markedly with all the other samples from the second time point. In summary, in some patients, viral diversity is as vast as the diversity that the whole set of known nonecotropic MLVs allows, and yet from another patient, an identical sequence was amplified 15 years later.…”
mentioning
confidence: 67%
“…An initial qualitative exploration of the dataset revealed that all but one of the chronic viruses (25 virus species) exhibited human-to-human transmission, with the single exception being simian foamy virus (although foamy viruses likely codiverge with other primate hosts) (29). In addition, it was notable that, of those viruses that establish a chronic infection, all had nonsegmented genomes and that the vast majority (20 species) had DNA genomes.…”
Section: Resultsmentioning
confidence: 99%